2021
DOI: 10.1002/ange.202107020
|View full text |Cite
|
Sign up to set email alerts
|

Synergistical Dipole–Dipole Interaction Induced Self‐Assembly of Phenoxazine‐Based Hole‐Transporting Materials for Efficient and Stable Inverted Perovskite Solar Cells

Abstract: Delicately designed dopant-free hole-transporting materials (HTMs) with ordered structure have become one of the major strategies to achieve high-performance perovskite solar cells (PSCs). In this work, we report two donor-p linkerdonor (D-p-D) HTMs, N01 and N02,which consist of facilely synthesized 4,8-di(n-hexyloxy)-benzo[1,2-b:4,5-b']dithiophene as a p linker,w ith 10-bromohexyl-10H-phenoxazine and 10-hexyl-10H-phenoxazine as donors,r espectively.T he N01 molecules form at wo-dimensional conjugated network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…16 In a study on the degradation of perovskite under the action of amide, Jeffrey et al demonstrated that the reduction of Pb 2+ was coordinated with amine first, and the oxidation-reduction process required the degradation of alkyl amine β-C-H bonds, revealing the interaction mechanism between amide and Pb 2+ from the chemical state. 17 The above work not only confirmed the feasibility of amide as an additive to assist in the deposition of highquality perovskite films but also revealed the significant contribution of amide additives to improve device stability. Additionally, due to the relative volatility of MA + (MA = methylammonium) cation, PSCs with MA + cation suffer from intrinsic instability at elevated temperature.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…16 In a study on the degradation of perovskite under the action of amide, Jeffrey et al demonstrated that the reduction of Pb 2+ was coordinated with amine first, and the oxidation-reduction process required the degradation of alkyl amine β-C-H bonds, revealing the interaction mechanism between amide and Pb 2+ from the chemical state. 17 The above work not only confirmed the feasibility of amide as an additive to assist in the deposition of highquality perovskite films but also revealed the significant contribution of amide additives to improve device stability. Additionally, due to the relative volatility of MA + (MA = methylammonium) cation, PSCs with MA + cation suffer from intrinsic instability at elevated temperature.…”
Section: Introductionsupporting
confidence: 58%
“…As a result, the device with 11MA delivered a champion PCE of 23.34% with outstanding ambient stability 16 . In a study on the degradation of perovskite under the action of amide, Jeffrey et al demonstrated that the reduction of Pb 2+ was coordinated with amine first, and the oxidation–reduction process required the degradation of alkyl amine β‐C‐H bonds, revealing the interaction mechanism between amide and Pb 2+ from the chemical state 17 . The above work not only confirmed the feasibility of amide as an additive to assist in the deposition of high‐quality perovskite films but also revealed the significant contribution of amide additives to improve device stability.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] Recently, self-assembled monolayers (SAMs) have been applied as very effective HSLs to replace conventional organic holetransporting materials such as PTAA and PEDOT:PSS, as SAMs benefit from their easily tuned energy level alignment with perovskite, minimized parasitic absorption, sufficient stability, and facile processibility that is compatible with low-cost and scalable production. [13][14] These SAM molecules usually consist of an anchor group that can bind with the substrates, a flexible spacer to provide sufficient rotational freedom for selfassembly, and a functional head group to facilitate efficient hole extraction. [15] Through rational molecular design, an ultra-thin and efficient HSL can be robustly formed on the ITO anode in inverted PSCs.…”
Section: Doi: 101002/adma202304415mentioning
confidence: 99%
“…[10][11] Recently, self-assembled monolayers (SAMs) have emerged as a class of highly effective HSLs in inverted PSCs, outperforming conventional hole-transporting materials (HTM) such as organic polymers like PTAA, PEDOT:PSS, and inorganic metal oxides like NiO x . [12][13] These SAM molecules usually consist of an anchor group, a spacer, and a head group. The anchor group of phosphonic acid or carboxylic acid can react with the hydroxy groups on the indium-tin oxide (ITO) surface to form an ultra-thin monolayer at the anode.…”
Section: Introductionmentioning
confidence: 99%